“COMPARATIVE STUDY OF HEPATOCELLULAR DYSFUNCTIONS BETWEEN PLASMODIUM FALCIPARUM AND PLASMODIUM VIVAX IN WEST BENGAL”. - DR. ASHIS KUMAR SAHA.,; DR. SOMNATH MAITRA,; DR. SUBHAS CHANDRA HAZRA., (International Journal of Pharma and Bio Sciences, 2014)
Aims: Our aim in this study was to compare the spectrum of hepatic damage between plasmodium falciparum and vivax. Materials and methods: From 228 (114 each for falciparum and vivax) diagnosed malaria patients, blood were collected for hematological, biochemical and serological tests (to exclude other causes of hepatitis). Data were collected and analyzed to compare severity between them. Results: In case of vivax affected females, serum bilirubin were raised, albumin and total protein were depressed significantly, whereas, in case of falciparum affected males, serum bilirubin, SGPT, SGOT, alkaline phosphatase were raised and total protein, albumin decreased significantly. In case of plasmodium falciparum affected patients, SGPT and alkaline phosphatase were elevated, whereas, serum albumin and prothrombin time were decreased significantly. In both groups, hemoglobin level was near normal. Conclusion: Falciparum was responsible for severe hepatocellular dysfunction. Hence, early detection of hepatic damage is necessary to prevent its future possible complications.